Pacemaker Lead Dislodgement Due to Left Shoulder Dislocation: A Case Report. Issue 3 (July 2018) - Kawai, Momotaro; Tanji, Atsushi; Nishijima, Takayuki; Tateyama, Koichi; Kamata, Yusaku; Urabe, Tadahisa
Abstract : Case: A 63-year-old man with a cardiac pacemaker presented with a left shoulder dislocation. His heart rate was 46 beats per minute, and pacemaker testing demonstrated an elevated pacing threshold, a decreased sensing threshold, and stable pacemaker lead impedance. Lead dislodgement due to the shoulder dislocation was suspected, and the patient underwent repositioning of the lead. Conclusion: When a patient with a pacemaker dislocates a shoulder, it should be confirmed that the heart rate is above the programmed lower rate of the pacemaker; electrocardiography should be performed, and the pacing parameters should be checked to ensure that pacing failure is not overlooked.